The effect of transnasal humidified rapid-insufflation ventilator exchange (THRIVE) versus nasal prongs on safe apnoea time in paralysed obese patients: a randomised controlled trial. (February 2022) - Guy, Louis; Christensen, Rebecca; Dodd, Ben; Pelecanos, Anita; Wyssusek, Kerstin; Van Zundert, Andre; Eley, Victoria A.
Abstract: Background: Evidence is lacking regarding the efficacy of Optiflow transnasal humidified rapid-insufflation ventilator exchange (THRIVE™) in obese patients. We compared the impact of this technique at 70 L min −1 with 4 L min −1 oxygen via nasal prongs on safe apnoea times of paralysed obese patients. Methods: We randomised adults with a BMI >35 kg m −2 undergoing elective bariatric surgery. While apnoeic and paralysed, Group T received 70 L min −1 oxygen via Optiflow THRIVE™. Group N received nasal prong oxygen at 4 L min −1 . The primary outcome was time to SpO2 ≤95% while apnoeic, with a 360 s cut-off. This was analysed by applying a time-to-event analysis. Results: Forty-two patients were included. The median (inter-quartile range) BMI was 44.8 kg m −2 (40.0–50.0) in Group T and 42.0 kg m −2 (39.3–45.1) in Group N. Median (inter-quartile range) time to SpO2 ≤95% in Group T was 356 (165 to ≥360) s and in Group N, 210 (160–270) s. Using a survival analysis framework, median time-to-event in Group T was 356 s (95% confidence interval 165 s–upper limit not defined) and 210 s (95% confidence interval 160–242 s) ( P =0.049) in Group N. Conclusions: Compared with oxygen delivered via nasal prongs at 4 L min −1, oxygen delivery via Optiflow THRIVE™ at a flow rate of 70 L min −1 can prolong safe apnoea time, however, the results are statistically inconclusive. Optiflow THRIVE™ did decrease the rate of reduction in P ao 2 during apnoea. Clinical trial registration: ANZCTR 12618000445279.